Postglacial Development of Kazakhstan Pine Forests - Kremenetski, Constantin; Tarasov, Pavel; Cherkinsky, Aleksandr (Géographie physique et Quaternaire, 1997)
ABSTRACTFossil pollen records from two peatlands and two lakes in Kazakhstan provide radiocarbon-dated evidence of vegetation change since 13 000 BP. During the Lateglacial open spruce (Picea obovata) forests started spreading along river valleys and over the Kazakhstan Foothills. By 9500 BP, the southern limit of spruce approached its present-day position. Between 9500 and 8000 BP steppe and open birch forests formed the vegetation in the south of the West Siberian Lowland. Dry steppe and semi-desert were the main types of vegetation in north Kazakhstan. From 7000 to 5500 BP Scots pine (Pinus sylvestris L.) expanded in Kazakhstan and reached its present day southern limit. Since 5500 BP pine has formed monospecific forests in the lrtysh-Semipalatinsk area and in the northern part of the Kazakhstan Foothills. By 5000 BP lime (Tilia cordata) penetrated into the northern part of the Kazakhstan Foothills. The ranges of oak (Quercus robur), elm (Ulmus glabra) and black alder (AInus glutinosa) also expanded. The period 4500-3600 BP was characterised by a drier and more continental climate. During that time, the forested area decreased. The ranges of broadleaved trees and alder were reduced. A phase of less continental climate occurred 3300-2800/ 2700 BP. By 1500 BP the present southern limit of Scots pine was established.